2021
DOI: 10.1007/s41207-021-00241-y
|View full text |Cite
|
Sign up to set email alerts
|

Soil geochemistry, edaphic and climatic characteristics as components of Tunisian olive terroirs: Relationship with the multielemental composition of olive oils for their geographical traceability

Abstract: Olive oil traceability based on the intrinsic chemical composition of the oil is becoming increasingly important due to the prevalence of fraudulent geographical labelling of olive oils. For a traceability tool to be valid, it should be based on olive oil properties that are clearly related to provenance factors. However, multielement analysis of the oil has been used as a traceability tool without any proof of a direct link between the multielemental composition and the geographical origin of the oil. In orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Based on the hypothesis that the mineral content of the soil in which the olives are grown dictates the multi-elemental composition of the resulting fruits [8,10,11,37], the use of ICP-AES and ICP-MS analytical techniques combined with chemometric tools, such as PCA, was evaluated to assess the applicability of these techniques for the determination of the geographical origin of olive products.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the hypothesis that the mineral content of the soil in which the olives are grown dictates the multi-elemental composition of the resulting fruits [8,10,11,37], the use of ICP-AES and ICP-MS analytical techniques combined with chemometric tools, such as PCA, was evaluated to assess the applicability of these techniques for the determination of the geographical origin of olive products.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have shown that trace elements' distribution in olives and olive oils depends on the mineral content and elemental bioavailability in the growing soil [6,8,10,11]. Therefore, the geochemical signature of the soil, which depends on the production area, is transferred to the olives [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, the assurance of authenticity, high quality and purity of olive oil is a matter of great importance. For this purpose, investigating olive oil by means of ICP-MS analysis gains widespread scientific attention [ 9 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 ]. A considerable amount of literature has been published on Spanish, Italian, Tunisian, and Greek olive oil varieties.…”
Section: Discussionmentioning
confidence: 99%